Program Percepatan Penurunan Stunting - Yuliawati, Widia; Widianingsih, Ida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to assess the effectiveness of the stunting reduction acceleration program in Tanjungsari Village, Karangpawitan District, Garut Regency, and identify factors that could hinder the effectiveness of implementing the program. The research method used is qualitative, with data obtained through interviews, observation and documentation. Data were analyzed using qualitative descriptive techniques. The results of the research show that the implementation of activities to accelerate stunting reduction in Tanjungsari Village is still not intended for young women, even though the target has been set for 495 young women, but it has not been realized, because according to the officials it is still not urgent to implement. Likewise, the program has not been implemented to target pregnant women and pregnant women with CED, who are actually a crucial group that influences the success of implementing this stunting program. This is due to the low understanding, skills and professionalism of the officers concerned, as well as the lack of access to information for program targets. In conclusion, the implementation of activities to accelerate stunting reduction in Tanjungsari Village is still not effective. Keywords: Effectiveness, Program, Stunting